2016
DOI: 10.1186/s13690-016-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Iodine in commercial edible iodized salts and assessment of iodine exposure in Sri Lanka

Abstract: BackgroundIodine is an essential micronutrient used by the thyroid gland in the production of thyroid hormones. Both excessive and insufficient iodine intakes can cause thyroid diseases thus harmful to the human body. Inadequate iodine intake by human body causes Iodine Deficiency Disorders (IDD) and hypothyroidism. Excessive iodine intake causes Iodine Induced Hyperthyroidism (IIH). Universal Salt Iodization (USI) is the most effective way of preventing IDD. This study determined the concentrations of iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…It was found that the total iodine content after drying the samples was most strongly correlated with the degree of hydration (r = 0.903) and the temperature of the impregnated samples (r = 0.99). This is also confirmed by previous studies [ 30 , 56 , 59 , 60 ]. The lowest stability of iodine was shown for samples impregnated at 4 °C.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that the total iodine content after drying the samples was most strongly correlated with the degree of hydration (r = 0.903) and the temperature of the impregnated samples (r = 0.99). This is also confirmed by previous studies [ 30 , 56 , 59 , 60 ]. The lowest stability of iodine was shown for samples impregnated at 4 °C.…”
Section: Resultssupporting
confidence: 93%
“…Impregnation time was also a factor affecting iodine content (r = 0.765). However, the significance of this factor depended on the degree of hydration and even more on the impregnation temperature [ 30 , 55 , 60 , 62 , 65 ]. The use of 1:4 hydration and impregnation temperature of 4 °C yielded total iodine ranging from 78 to 97%.…”
Section: Resultsmentioning
confidence: 99%
“…The content of iodate in the solution was determined by the iodometric titration method as a standard method according to the procedure given in the previous literature. 92 The measurements were performed using the standard addition method, by SWV in the potential range from 0 to −1.0 V, scan rate 50 mV s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The content of iodate in the solution was determined by the iodometric titration method as a standard method according to the procedure given in the previous literature. 92 The measurements were performed using the standard addition method, by SWV in the potential range from 0 to À1.0 V, scan rate 50 mV s À1 . The standard solutions of iodate were injected into the real samples to check the recovery percent of added iodate (found value/intrinsic value).…”
Section: Analytical Applications For Real Samplementioning
confidence: 99%
“…The iodide content was measured using an iodide combination electrode [23]. Salt (2 g) was dissolved in 10 ml of distilled water.…”
Section: Determination Of Iodate Content Of Iodized Saltmentioning
confidence: 99%